Pengaruh Literasi Keuangan, Modal Usaha Dan Digitalisasi Terhadap Keberlanjutan Usaha Mikro Kecil dan Menengah (UMKM) Di Kecamatan Abiansemal Kabupaten Badung - Ni Nyoman Triantini; Cokorda Gde Bayu Putra; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in enhancing local economic growth. MSME sustainability has become a strategic issue as it relates to the ability of business to survive and develop in the long term amid increasing competition and rapid technological advancement. Despite their considerable potential, MSMEs continue to face various challenges, including limited business capital, low levels of financial literacy, and the suboptimal utilization of digital technology in operational and marketing activities. The composition of MSMEs in Abiansemal Subdistrict is predominantly micro enterprises, totaling 5,290 units, while small and medium enterprises account for 121 units and 14 units, respectively. This condition indicates that most MSME actors operate on a limited scale in terms of assets, turnover, production capacity, and competitiveness. This study aims to analyze the effect of financial literacy, business capital, and digitalization on MSME sustainability in Abiansemal Subdistrict, Badung Regency. This research employs a quantitative approach with a population of 5,425 MSMEs. The sample consists of 99 respondents selected using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results reveal that financial literacy, business capital, and digitalization have a positive and significant effect on MSME sustainability.